Evolution à moyen terme d'un écosystème estuarien : le bassin de Marennes-Oléron - Soletchnik, Patrick (Présentation Journées du Département des Ressources Aquacoles, La Tremblade, 17-18 juin 2002, 2002)
The Marennes Oléron Bay, the main French oyster culture basin, is an estuarine zone which is subject to anthropic pressure. Meteorological parameters such as temperature, insolation, pluviometry determine, for the most part, the water temperature and salinity conditions for each season and control the nutrient fluxes, as well as the primary and secondary production of the basin. The average air temperature (Météo -France) stays around 12.5°C between 1950 and 1980, then rises more than 1°C in 20 years. In those 50 years, average insolation drops from 198 hours to 176 hours, corresponding to an 11% decrease. Seasonal distribution of water inputs shows that spring pluviometry increased by 30% between the 1950's and the last two decades. Precipitations also show a shift in seasons and in the distribution of their quantity over the last decades. These medium term evolutions intensify over the last two decades and have consequences on the estuarine ecosystem. This study shows that the primary production peaks (phytoplanktonic blooms), oysters' main food supply, have slowly shifted from May to June over the last 3 decades. Temperature and trophic resource are determining factors for the oyster C.gigas.'s growth and reproduction. A study conducted in 2000 on 4 on-bottom and off-bottom oyster populations is a good example of the "discontinuity" in the yolk formation that has often been met for the last few years. Slowing down of the yolk formation because of late or staggered phytoplanktonic blooms, "biological antagonism" affecting oysters, and (or?) physiological dysfonctioning causing the oyster to be "tired" during maturation (alternance of different metabolic energetic routes), are the different paths that need to be explored in order to understand summer mortality. This "unthrifty" physiological behaviour could be the adaptive answer of Crassostrea gigas to climatic evolution. The temperature rise and the insolation drop have antagonistic effects on metabolism: the first one accelerates the gametogenesis and the ...